Sequential Treatment with an Immune Checkpoint Inhibitor Followed by a Small-Molecule Targeted Agent Increases Drug-Induced Pneumonitis - Jung, Jongheon; Kim, Hyae Young; Kim, Dong-Gil; Park, Seog Yun; Ko, A Ra; Han, Ji-Youn; Kim, Heung Tae; Lee, Jin Soo; Lee, Youngjoo (Cancer research and treatment, 2021)
PurposeImmune checkpoint inhibitors (ICI) and targeted small-molecule drugs are mainstay elements of lung cancer chemotherapy. However, they are associated with development of pneumonitis, a rare, but potentially life-threatening event. We analyzed lung cancer patients treated with ICI to evaluate the effect of sequential therapeutic administration on the incidence of pneumonitis. Materials and MethodsIn this retrospective study, 242 patients were included. Serial radiologic findings taken during and immediately after ICI treatment were reviewed. Factors that increased pneumonitis and the relationship between peri-ICI chemotherapy and the development of pneumonitis were evaluated. ResultsPneumonitis developed in 23 patients (9.5%); severe pneumonitis (grade ≥ 3) occurred in 13 of 23 patients (56%); pneumonitis-related death occurred in six. High-dose thoracic radiation (≥ 6,000 cGy) revealed a tendency toward high risk of pneumonitis (odds ratio, 2.642; 95% confidence interval, 0.932 to 7.490; p=0.068). Among 149 patients followed for ≥ 8 weeks after the final ICI dose, more patients who received targeted agents within 8-weeks post-ICI experienced pneumonitis (3/16, 18.8%) compared with patients who received cytotoxic agents (4/54, 7.4%) or no chemotherapy (4/79, 5.1%) (p=0.162). Targeted therapy was associated with earlier-onset pneumonitis than treatment with cytotoxic agents (35 vs. 62 days post-ICI, p=0.007); the resulting pneumonitis was more severe (grade ≥ 3, 100% vs. 0%, p=0.031).ConclusionSequential administration of small-molecule targeted agents immediately after ICI may increase the risk of severe pneumonitis. The sequence of chemotherapy regimens that include ICI and targeted agents should be carefully planned to reduce the risk of pneumonitis in lung cancer patients.